Light Chain Proximal Tubulopathy: Expanding the Pathologic Spectrum with and without Deposition of Crystalline Inclusions. (30th August 2012) - Sharma, Shree G.; Bonsib, Steven M.; Portilla, Didier; Shukla, Ashutosh; Woodruff, Adam B.; Gokden, Neriman
Abstract : Light chain proximal tubulopathy (LCPT) is an uncommon form of renal disease associated with dysproteinemias. It is characterized by intracytoplasmic deposition of crystallized mostly kappa monoclonal light chains in proximal tubules (PTs). Crystals are located within lysosomes by electron microscopy (EM). Rare lambda LCPT cases without crystals by EM were described. Retrospectively, we reviewed clinical, light microscopic (LM), immunofluorescence (IF), and EM findings in 9 cases) (8 males, 1 female; mean age 57 years (38–81)) with multiple myeloma. LM showed abundant cytoplasmic droplets in PT cells in all cases. Droplets were also present in the podocytes, endothelial and parietal cells in one case. IF revealed staining of crystals with kappa in 3 and lambda in 6. EM showed electron dense rectangular, rhomboid, or needle shaped crystals in PT cells in 3 cases (33%), one of which had crystals in podocytes and interstitial cells. Six lambda LCPT cases showed no crystals by EM (67%). This may reflect differences in the physicochemical properties of light chains. The mechanisms of crystal accumulation in these cells and the significance of this finding are unknown.